KAJIAN PENGARUH TATA GUNA LAHAN TERHADAP KINERJA JALAN PADA KAWASAN PENDIDIKAN, SEMARANG - Turyanto, Turyanto; Sugalih, Sugalih; Irawati, Iin (FSTPT Indonesia, 2015)
Along with the development of science and technology, transportation needs will also increase, especially in urban areas. If high kedaraan population is not matched by adequate roads will give rise to problems such as traffic congestion. To overcome this we need to hold a good traffic management. From the results of the traffic survey carried out for three days in a row on the road Hayam Wuruk which has the function of land use, one of them in the form of educational areas, namely the Diponegoro University Graduate. The educational function of the area led to the function of other land uses such as commercial areas (potokopian, food stalls, street vendors), which often occurs as a result of vehicles queuing or delay of the side barriers. The method should be used for the analysis is the Indonesian Highway Capacity Manual (MKJI) 1997. The results of the performance analysis of survey data for three days on the road Hayam Wuruk have approached saturation, namely the DS of 0.245, 0.473, 0.622 as the influence of the side barriers.